PENINGKATAN KAPASITAS PETANI NILAM DALAM PEMBIBITAN MELALUI KEGIATAN PENGABDIAN DI DESA TEULADAN, KABUPATEN ACEH BESAR - Raichan Izzati (LPPM Universitas Abdurrab, 2025)
This community service activity aimed to improve the knowledge and skills of farmers in patchouli (Pogostemon cablin Benth.) seedling techniques in Teuladan Village, Lembah Seulawah Subdistrict, Aceh Besar District. The training was conducted by a team from Universitas Syiah Kuala through counseling, demonstration, and hands-on practice methods. One of the innovations introduced was the use of Trichoderma as a biological agent in the initial treatment of cuttings to enhance growth success and prevent disease attacks. Prior to the activity, farmers collaboratively built a seedling nursery as a form of active participation. The training resulted in improved farmer competence in independently propagating patchouli seedlings, with a total of 2,600 seedlings successfully prepared and maintained. This activity is expected to serve as an initial step toward seed self-sufficiency and the development of a patchouli-based agribusiness in the area.